Visible light : data communications and applications - Haigh, Paul Anthony (IOP series in emerging technologies in optics and photonics., 2020)
This book offers an overview of the state-of-the-art of visible light communication (VLC) systems across emerging areas of increasing importance within the field. It is divided into two parts, with the first describing the latest developments in data communication using VLC technologies. It includes the fundamental mechanics of the semiconductor light-emitting diodes (LEDs) used in academic and commercial systems, areas of high-speed circuit design including circuit diagrams and small-signal analysis. Exotic modulation formats and digital signal processing including machine learning architectures are then covered before the book looks at emerging areas within the VLC research community, including colour balancing and colour-based modulation. The second part of the book looks at applications that do not consider indoor data communication in general, such as localisation/positioning, sensing and the intelligent transport systems paradigm. Finally, the completely new area of oxygen sensing is also included with the aim of inspiring researchers to test news fields and apply ideas across domains. Part of IOP Series in Emerging Technologies in Optics and Photonics.